New Opportunities for Air Cathode Batteries; in-Situ Neutron Diffraction Measurements - Jacas Biendicho, Jordi; Noréus, Dag; Offer, Colin; Svensson, Gunnar; Smith, Ronald I.; Hull, Stephen (Frontiers in Energy Research, 2018)
Batteries with air electrodes are gaining interest as Energy Storage Systems (ESSs) for Electrical Vehicles (EVs) because of their high specific energy density. The electrochemical performance of these batteries is limited by the metallic electrode, which suffers structural transformations and corrosion during cycling that reduces the cycle life of the battery. In this context, relevant information on the discharge products may be obtained by in-situ neutron diffraction, a suitable technique to study electrodes that contain light elements or near neighbor elements in the periodic table. Case studies of MH-air and Fe-air batteries are highlighted.